Utilization of Host Cell Chromosome Conformation by Viral Pathogens: Knowing When to Hold and When to Fold - Majumder, Kinjal; Morales, Abigail J. (Frontiers in Immunology, 2021)
Though viruses have their own genomes, many depend on the nuclear environment of their hosts for replication and survival. A substantial body of work has therefore been devoted to understanding how viral and eukaryotic genomes interact. Recent advances in chromosome conformation capture technologies have provided unprecedented opportunities to visualize how mammalian genomes are organized and, by extension, how packaging of nuclear DNA impacts cellular processes. Recent studies have indicated that some viruses, upon entry into host cell nuclei, produce factors that alter host chromatin topology, and thus, impact the 3D organization of the host genome. Additionally, a variety of distinct viruses utilize host genome architectural factors to advance various aspects of their life cycles. Indeed, human gammaherpesviruses, known for establishing long-term reservoirs of latent infection in B lymphocytes, utilize 3D principles of genome folding to package their DNA and establish latency in host cells. This manipulation of host epigenetic machinery by latent viral genomes is etiologically linked to the onset of B cell oncogenesis. Small DNA viruses, by contrast, are tethered to distinct cellular sites that support virus expression and replication. Here, we briefly review the recent findings on how viruses and host genomes spatially communicate, and how this impacts virus-induced pathology.